Preclinical models of immune checkpoint inhibitors-related interstitial pneumonia for anti-PD1 tumor immunotherapy - Tingyue Luo; Weisheng Chen; Danhui Huang; Xiguang Liu; Junjie Xi; Zeyu Fu; Junwei Chen; Yuhan Du; Ruijun Cai; Qi Yu; Dongyu Liu; Jiangzhou Du; et al. (Immunobiology)
Immune-related adverse reactions (irAEs) are common adverse reactions after immune checkpoint inhibitor treatment, impacting the universality and continued use of immunotherapy. Currently, preclinical models to investigate the mechanisms underlying these adverse effects are inadequate. This study aims to develop both in vitro and in vivo models of irAEs to advance basic research on these adverse reactions. For vitro models, we designed two co-culture systems: “Lung epithelial cells-PBMC” conditional co-culture model and “organoid-PBMCs” co-culture model. These involve culturing spheroids, patient-derived organoids and isolating, expanding, and co-culturing peripheral blood mononuclear cells (PBMCs). For vivo model, PD1 humanized mice were used to establish a lung carcinoma in situ model in offspring, with blocked immune checkpoints to induce systemic inflammatory responses. Mice without PD-1 blockade served as the control group. In both organoid and “lung epithelial cell-PBMC” models, compared with the control group, the PBMC+anti-PD1 group exhibited inflammatory injury, demonstrated by the worst activity, increased collagen deposition, elevated mRNA levels of αSMA and Vimentin, higher Fibronectin expression, and higher inflammatory factors (IL6, IL1β, MPO) in the culture supernatant (p < 0.05). In vivo model also showed pulmonary inflammation, with slower weight gain of the affected mice, more obvious pulmonary interstitial thickening(Masson staining and α-SMA immunofluorescence staining), and increased immune cells and IL17A in alveolar lavage fluid and serum. This study successfully developed preclinical models of irAEs using organoid technology, conditioned co-culture and humanized mouse models, effectively reproducing inflammatory injury and offering valuable tools for irAE research.